2008
DOI: 10.1097/fjc.0b013e31815ab4b6
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Activity of Epigallocatechin Gallate Is Mediated by the Inhibition of PLCγ2 Phosphorylation, Elevation of PGD2 Production, and Maintaining Calcium-ATPase Activity

Abstract: We have previously reported that green tea catechins displayed a potent antithrombotic effect by inhibition of platelet aggregation. In the present study, the antiplatelet and antithrombotic activities of epigallocatechin gallate (EGCG), the major catechin derived from green tea, were extensively investigated. EGCG inhibited arterial thrombus formation and U46619-, collagen-, and arachidonic acid (AA)-induced washed rabbit platelet aggregation in a concentration-dependent manner, with IC50 values of 61 +/- 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Many of the studies on platelet aggregation have been carried out using various animal platelets. In addition to showing that green tea catechins were involved in inhibition of platelet aggregation, studies suggested that catechins may affect several cellular targets that are related to platelet activation, including: through the arachadonic acid pathway, inhibition of a cytoplasmic increase in calcium, decreased thrombaxane A 2 (TXA 2 ) production, and inhibition of cyclooxygenase-1 (COX)-1 [90][91][92][93]. A study using human platelets concluded that EGCG was able to inhibit platelet activation by adenosine diphosphate (ADP) stimulation, and suppressed the p38 MAPK phosphorylation of heat shock protein 27 (HSP27), which would inhibit the release of pro-thrombotic contents from platelets [94].…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…Many of the studies on platelet aggregation have been carried out using various animal platelets. In addition to showing that green tea catechins were involved in inhibition of platelet aggregation, studies suggested that catechins may affect several cellular targets that are related to platelet activation, including: through the arachadonic acid pathway, inhibition of a cytoplasmic increase in calcium, decreased thrombaxane A 2 (TXA 2 ) production, and inhibition of cyclooxygenase-1 (COX)-1 [90][91][92][93]. A study using human platelets concluded that EGCG was able to inhibit platelet activation by adenosine diphosphate (ADP) stimulation, and suppressed the p38 MAPK phosphorylation of heat shock protein 27 (HSP27), which would inhibit the release of pro-thrombotic contents from platelets [94].…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…The platelet concentration was counted using a Coulter Counter (Coulter Electronics, Hialeah, FL, USA) and adjusted to 4 10 8 platelets per milliliter. Platelet aggregation was measured as previously described 20) . Briefly, washed platelet suspensions were incubated at 37 in the aggregometer with stirring at 1000 rpm.…”
Section: Measurement Of Washed Rabbit Platelet Preparation and Aggregmentioning
confidence: 99%
“…Thromboxane B2, prostaglandin D2 and 12-HETE generations were measured as previously described 20) . Briefly, washed rabbit platelets (4 10 8 platelets/mL) were preincubated with various concentrations of obovatol at 37 for 5 min and then further incubated with a mixture of [ 3 H]-AA (1 Ci/mL) and unlabeled AA (2 M) for 5 min.…”
Section: Measurement Of Thromboxane B2 Prostaglandin D2 and 12-hetementioning
confidence: 99%
See 2 more Smart Citations